PENERAPAN MODEL KOOPERATIF TIPE JIGSAW BERBANTUAN APLIKASI WORDWALL UNTUK MENINGKATKAN KEAKTIFAN SISWA PADA PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Afsan, Mhd Febri; Arsil, Arsil; Destrinelli, Destrinelli (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
This study aims to describe the implementation of the cooperative learning model of the jigsaw type, assisted by the Wordwall application, to enhance student engagement of fourth-grade science learning at SDN 55/I Sridadi. The research conducted through a classroom action research design. Data were collected through observation, interviews, and documentation, and analyzed both qualitatively and quantitatively. The study was conducted over two cycles, with four stages in each cycle: planning, implementation, observation, and reflection. The results show that applying the jigsaw cooperative model, supported by the Wordwall application in science learning, successfully increased student engagement. It was evident as student engagement improved across all indicators in each meeting cycle. In the first cycle, student engagement was classified as "fair," with a percentage of 60.26%, but after improvements in the second cycle, it increased to "good," reaching a percentage of 84.73%. Based on the findings, it can be concluded that implementing the jigsaw cooperative model with the help of the Wordwall application in science learning can effectively enhance student engagement.